OBSERVAÃ‡ÃƒO SOBRE O CAPIM ð˜‰ð˜³ð˜¢ð˜¤ð˜©ð˜ªð˜¢ð˜³ð˜ªð˜¢ ð˜¥ð˜¦ð˜¤ð˜¶ð˜®ð˜£ð˜¦ð˜¯ð˜´, IRRIGADO NA Ã‰POCA DE VERÃƒO E DE INVERNO - Gheifi Filho, Hugo (REVISTA DE AGRICULTURA, 2020)
OBSERVAÃ‡ÃƒO SOBRE O CAPIM ð˜‰ð˜³ð˜¢ð˜¤ð˜©ð˜ªð˜¢ð˜³ð˜ªð˜¢ ð˜¥ð˜¦ð˜¤ð˜¶ð˜®ð˜£ð˜¦ð˜¯ð˜´, IRRIGADO NA Ã‰POCA DE VERÃƒO E DE INVERNO